The contextuality of the Qur'an in detecting diseases (Study of the interpretation of eye diseases of Prophet Ya'qub in Surah Yusuf verse 84 perspective of eye health) - Khoirul Amirudin, Mukamat; Hakim, Lukmanul; Koma, Windy Aisty; Rahmasari, Luthfiana Devi Erica; Khotimah, Husnul (Jurnal Indonesia Sosial Sains, 2023)
Qur'an Chapter Yusuf verse 84 tells about the sore eye of Prophet Ya'qub. It is told that he had sore eye with an indication of white discoloration of his eyes due to deep sadness. In this verse, the Qur'an only speaks of the nature and cause of the illness, without mentioning the type of illness yet. Based on this background, this thesis presents research on the eye disease of Prophet Ya'qub in the perspective of eye health study. The research method applied in the study is qualitative method. Whereas, The documentation techniques from library sources in the form of 12 books of tafsir muktabar along with other supporting books for data collection techniques. Then the interpretation analysis theory that is applied is tahli>li> interpretation. The results of the study found that there are six opinions of tafsir scholars in interpreting the type of eye disease of Prophet Ya'qub. The six are: blindness, low vision, flooding of tears (Nasolacrimal duct obstruction), thin white membrane (cataract), dry eye, and glaucoma. There are two principles which become the standard in the object of this research, namely the indication of the white color in the eyes of Prophet Ya'qub and sadness as a causative factor. According to the study of eye health, by paying attention to these two indications, the author further strengthens the opinion that the eye disease which plagued the Prophet Ya'qub leads to cataract eye disease. Because cataracts are a disease which clearly gives a white effect on the eye. As for the other diseases, there is less visible characteristic of the white effect on the eye. Furthermore, the main cause of cataracts is excess sugar in the body (Diabetes Mellitus). Diabetes mellitus often occurs due to stress or protracted sadness. Thus, the author's strong assumption in giving the conclusion that the eye disease experienced by the Prophet Ya'qub is leading to cataract eye disease